2007
DOI: 10.1007/s11162-007-9060-9
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effects of Financial Aid on the Gap in Student Dropout Risks by Income Level

Abstract: Using national survey data and discrete-time logit modeling, this research seeks to understand whether student aid mediates the relationship between parental income and student dropout behavior. Our analysis confirms that there is a gap in dropout rates for lowincome students compared with their upper income peers, and suggests that some types of aid are associated with lower risks of dropout. Thus, we examine the interaction between financial aid type and parental income to explore whether, and if so how, dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0
13

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(76 citation statements)
references
References 27 publications
(29 reference statements)
3
60
0
13
Order By: Relevance
“…Además, encuentran que aquellos estudiantes que cuentan con algún tipo de beneficio financiero, presentan una menor probabilidad de desertar, destacando el Crédito con Aval del Estado (CAE). Por su parte, Barrios et al (2011) estudian el efecto de los beneficios financieros sobre los resultados académicos, encontrando que el sistema de financiamiento con CAE es más eficiente que las becas y otros créditos en disminuir las tasas de deserción, contrario a lo propuesto por Chen y DesJardins (2008, 2010.…”
Section: Introductionunclassified
“…Además, encuentran que aquellos estudiantes que cuentan con algún tipo de beneficio financiero, presentan una menor probabilidad de desertar, destacando el Crédito con Aval del Estado (CAE). Por su parte, Barrios et al (2011) estudian el efecto de los beneficios financieros sobre los resultados académicos, encontrando que el sistema de financiamiento con CAE es más eficiente que las becas y otros créditos en disminuir las tasas de deserción, contrario a lo propuesto por Chen y DesJardins (2008, 2010.…”
Section: Introductionunclassified
“…Astin (2005) found that completing the baccalaureate degree in four years was positively and significantly related to father's education level. Correlated with parental education level, Pell Grant eligibility is based on a student's estimated family contribution (EFC) to financially support their education (Chen & Desjardins, 2008;Lips, 2011;Mahan, 2011) and can also be used as a proxy for SES.…”
Section: General Populationmentioning
confidence: 99%
“…For many researchers financial challenges are believed to be one of the primary causes for students leaving an institution (Chen & Desjardins, 2008;Tinto, 1975). Even though no study will be able to understand all the leaving behaviors of college students, Janasiewicz (1987) was determined to recognize the leaving behavior of students at Florida State University.…”
Section: Factors That Impact College Student Attritionmentioning
confidence: 99%